Pengaruh Pembelajaran Blended Learning Terhadap Motivasi Belajar Anak Di Sanggar Pelita - Farhan Muhammad Irsyadi; Tuti Atika (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2022)
Early adolescence is a period of many changes in children both physically and mentally. During this period, there were many changes in the interactions experienced by individuals and both their families and their social environment. Usually the child will begin to explore himself more which is usually done with his playmates, but on the other hand he will also begin to feel the need for privacy so that he likes to be alone from his family. In a pandemic situation like this, there is a slight shift in children's social interactions, smartphones are an inseparable part of their daily lives, and even become a necessity because they are needed in their education process at school. So that they can no longer be separated from the internet, smartphones and other related things because it has become a habit for them. In this case, the PKL (Field Work Practice) activities to increase children's learning requests that I do will take advantage of this situation through the blended-learning method, which is a learning method that combines online and offline learning using the casework method through several stages consisting of Engagement intake Contract, Assessment. Planning/planning. Evaluation and Termination of Interventions. The focus in this case is to increase children's interest and motivation in learning by utilizing technological advances which have become an inseparable part since the COVID-19 pandemic began.